1991
DOI: 10.1002/cyto.990120102
|View full text |Cite
|
Sign up to set email alerts
|

Cytophotometric analysis of corresponding cytological and histological cervical intraepithelial neoplasia grade III specimens

Abstract: Cytophotometric analysis of cervical intraepithelial neoplasia grade I11 (CIN 111) was performed in 22 cytological smears (CS) and in 22 corresponding cytospin specimens retrieved from selected areas of paraffin-embedded tissues (PEC). The average time interval between cytological and histological diagnosis was 6 weeks. CIN I11 nuclei in CS and PEC specimen were Thionin-Feulgen stained and digitized. Beside the visual classification of DNA ploidy patterns, the 2 . 5~ and 5c exceeding rates and the specimen mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…DNA profiling of cervical cytology and biopsy samples has been proposed by a number of investigators who have found such studies to be informative for classification of lesions 2,3,12,14,19,20 and for the predicition of progressive behavior. 4,18 Visual classification of profile histograms has been used as have derived parameters, such as the 2c deviation index and the 5c exceeding rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA profiling of cervical cytology and biopsy samples has been proposed by a number of investigators who have found such studies to be informative for classification of lesions 2,3,12,14,19,20 and for the predicition of progressive behavior. 4,18 Visual classification of profile histograms has been used as have derived parameters, such as the 2c deviation index and the 5c exceeding rate.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]12,14,16,19,20,22 Although the DNA profile values in conventional smears show a good correlation with those obtained from disaggregated cervical biopsies, lack of complete concordance has been noted. 20 The availability of liquid-based, thin-layer cytology presents the pathologist with the opportunity to obtain additional cells to examine in the case of ambiguous samples or for ancillary studies without committing the sole diagnostic slide to the procedure. We previously found such liquid-based samples to be stable for extended periods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For cervical smears, a good discrimination between control samples and dysplasia can also be reached by determination of the DNA content (Atkin & Kay, 1979;Frielander et aI., 1984) by image analysis (Bibbo et al, 1985;Hanselaar et al, 1991;Deleener et aI., 1991). Several studies have demonstrated that the preneolastic stages showed a much higher DNA content (polyploidisation with subsequent aneuploidization) than the normal cervical smears (Bibbo et aI., 1985;Hanselaar et al, 1991;Deleener et al, 1991).…”
Section: Aberrations In Cervical Cancermentioning
confidence: 99%
“…Several studies have demonstrated that the preneolastic stages showed a much higher DNA content (polyploidisation with subsequent aneuploidization) than the normal cervical smears (Bibbo et aI., 1985;Hanselaar et al, 1991;Deleener et al, 1991).…”
Section: Aberrations In Cervical Cancermentioning
confidence: 99%